Graciela Batticuore. El taller de la escritora. Veladas literarias de Juana Manuela Gorriti : Lima-Buenos Aires (1876/1877-1892), Rosario, Beatriz Viterbo, 1999, 233 páginas. - Quintana, Isabel Alicia (Universidad Nacional de Quilmes, 2000)
Fil: Quintana, Isabel Alicia. Universidad de Buenos Aires; Argentina.